Investigation the contribution of process areas to lower back pain among manual assembly workers in medical device industry - Mohammad Syukur, Md Noh; Saiful Anwar, Che Ghani; Wan Sharuzi, Wan Harun (Institution of Engineering and Technology, 2022)
Work-related musculoskeletal disorders are the leading cause of occupational health issues in manufacturing, especially for manual assembly processes. One of the primary prevalence of work-related musculoskeletal disorders among manual assembly workers in the medical device industry is low back pain. This paper investigated the risk factors associated with process areas on the low back pain cases among manual assembly workers in one multinational medical device company. This report represents the second of three stages of an investigation study; namely validation of risk factors. Interview sessions were conducted with six manual assembly workers who obtained the highest musculoskeletal disorder scores of low back pain in the earlier study. Results of the interviews were characterized into three major risk factors; lifting weights during work, chair condition and working posture. These three risk factors were then validated with a larger group of 153 female participants of the same population using Cornell Musculoskeletal Discomfort Questionnaire and an additional self-administered questionnaire. The results show that lifting weights during work and chair conditions have the highest risk of low back pain with each 48% prevalence, while the risk due to working posture is lower at 17%. The study's outcome will be used in the third stage of the investigation study, that is, to formulate improvement actions with ergonomics specialists.